Bile canaliculi contract autonomously by releasing calcium into hepatocytes via mechanosensitive calcium channel. (November 2020) - Gupta, Kapish; Ng, Inn Chuan; Balachander, Gowri Manohari; Nguyen, Binh P.; Tucker-Kellogg, Lisa; Low, Boon Chuan; Yu, Hanry
Abstract: Drug-induced hepatocellular cholestasis leads to altered bile flow. Bile is propelled along the bile canaliculi (BC) by actomyosin contractility, triggered by increased intracellular calcium (Ca 2+ ). However, the source of increased intracellular Ca 2+ and its relationship to transporter activity remains elusive. We identify the source of the intracellular Ca 2+ involved in triggering BC contractions, and we elucidate how biliary pressure regulates Ca 2+ homeostasis and associated BC contractions. Primary rat hepatocytes were cultured in collagen sandwich. Intra-canalicular Ca 2+ was measured with fluo-8; and intra-cellular Ca 2+ was measured with GCaMP. Pharmacological modulators of canonical Ca 2+ -channels were used to study the Ca 2+ -mediated regulation of BC contraction. BC contraction correlates with cyclic transfer of Ca 2+ from BC to adjacent hepatocytes, and not with endoplasmic reticulum Ca 2+ . A mechanosensitive Ca 2+ channel (MCC), Piezo-1, is preferentially localized at BC membranes. The Piezo-1 inhibitor GsMTx-4 blocks the Ca 2+ transfer, resulting in cholestatic generation of BC-derived vesicles whereas Piezo-1 hyper-activation by Yoda1 increases the frequency of Ca 2+ transfer and BC contraction cycles. Yoda1 can recover normal BC contractility in drug-induced hepatocellular cholestasis, supporting that Piezo-1 regulates BC contraction cycles. Finally, we show that hyper-activating Piezo-1 can be exploited to normalize bile flow in drug-induced hepatocellular cholestasis.